2011
DOI: 10.1002/srin.201100034
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments and Mid‐ and Long‐Term CO2 Mitigation Projects in Ironmaking

Abstract: CO 2 mitigation and the stable supply of raw materials are two major issues for the steel industry. The Japanese steel industry has promoted short term developments and investments to comply with the Japan Iron and Steel Federation's voluntary action plan in parallel with developing plans for drastic CO 2 mitigation programs toward the post Kyoto protocol period. This paper describes short-term measures in the ironmaking field such as natural gas injection technology to the sintering bed and burden distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…For example, the European Community has developed ULCOS (Ultra-Low CO 2 Steelmaking), a comprehensive program to determine the most suitable technologies for the future. 1) In Japan, there are substantial short-term 2) and long-term (COURSE50) 3) projects. More broadly, the World Steel Association draws together international efforts under its CO 2 Breakthrough Program, including the Australian program, which is jointly conducted by BlueScope Steel, OneSteel and CSIRO.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the European Community has developed ULCOS (Ultra-Low CO 2 Steelmaking), a comprehensive program to determine the most suitable technologies for the future. 1) In Japan, there are substantial short-term 2) and long-term (COURSE50) 3) projects. More broadly, the World Steel Association draws together international efforts under its CO 2 Breakthrough Program, including the Australian program, which is jointly conducted by BlueScope Steel, OneSteel and CSIRO.…”
Section: Introductionmentioning
confidence: 99%
“…1 The four ULCOS solutions selected for the continuation of the ULCOS program, according to Birat et al [10] It is worth noting that other substantial initiatives have taken place in Japan as extensions of ''Ishii Project''. These have been reviewed by Takeda et al [14].…”
Section: Course 50mentioning
confidence: 99%
“…Furthermore, the reaction efficiency of BF is improved, fuel ratio is reduced, and CO 2 emission is reduced . In general, the iron coke is prepared by co‐carbonizing the mixtures of iron ore and coal . During the carbonization, the iron oxide is reduced to metallic iron, which can act as a catalyst in the gasification reaction of carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, iron coke with iron ore up to 30% still has enough drum strength I10600 of above 80% for use in BF. Takeda et al found that when the addition ratio of iron ore is more than 30%, the mechanical strength of ferro‐coke prepared by briquetting–shaft process remarkably decline, whereas the reactivity increases linearly with the addition of iron ore. Furthermore, it was indicated by Nomura et al that the reactivity of iron coke prepared by coke oven process can be evidently improved with the addition of iron ore, but the drum strength DI15150 is decreased.…”
Section: Introductionmentioning
confidence: 99%